Application of the Numbered Head Together (NHT) Model Assisted by Crossword Media to Increase Interest in Learning in History Learning at XI SMAN 5 Tualang - Indriani, Lala; Bunari, Bunari; Suroyo, Suroyo (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This research discusses the application of the Numbered Head Together (NHT) model assisted by crossword puzzles to increase learning interest in history learning at XI SMAN 5 Tualang. The aim of this research is to determine the application of the NHT model, teacher and student activities, as well as increasing interest in learning with the help of crossword puzzles to increase interest in learning in class XI history learning at SMAN 5 Tualang. This research uses a Classroom Action Research (PTK) approach where the research takes the form of action in the form of a series of activity cycles for students. By carrying out corrective actions using the Numbered Head Together (NHT) learning model, teacher activity can be increased with a percentage in cycle I of 52.50% in the quite good category, then increasing in cycle II to 91.25% in the very good category. Furthermore, by carrying out corrective actions by utilizing Numbered Head Together (NHT) it can increase the activities of class XI 5 students at SMA Negeri 5 Tualang. In the first cycle of student activities, the percentage was 51.87% in the good category, then it increased in the second cycle to 88.69% in the very good category. The use of the Numbered Head Together (NHT) learning model can increase students' interest in learning with a percentage in the first cycle of 66.67% with the performance not being successful and increasing in the second cycle by 87.66%. This means that students' interest in learning has reached the success indicator, namely ≥75%